Prolonged light and thermal stress effects on industrial dye-sensitized solar cells: A micro-raman investigation on the long-term stability of aged cells - V. Likodimos; Stergiopoulos, T.; P. Falaras; Harikisun, R.; Desilvestro, J.; Tulloch, G. (Journal of Physical Chemistry C, 2009)
Micro-Raman spectroscopy is applied to investigate the long-term stability of industrial dye-sensitized solar cells under prolonged light soaking and thermal stress following continuous illumination over 6450 h at 55-60 °C. The Raman spectral characteristics of the individual cell components have been investigated using two excitation wavelengths in the visible and near-infrared range allowing us to assess the microstructure of the TiO2/conducting glass photoelectrode, the chemical bonding of the hydrophobic Ru(II)-polypyridyl dye complex on the mesoporous TiO2 film, and the electrolyte composition. Comparative ex situ resonance Raman measurements on fresh and aged cells indicate minor differences in the vibrational characteristics of the triiodide, dye molecules, and the triiodide/dye charge transfer adduct at the electrode/electrolyte interface upon aging, confirming the absence of any distinct chemical modification that could create instability. In situ Raman experiments implemented via the application of a polarization bias reveal a less pronounced potential dependence of both the electrolyte and the dye Raman response for the aged cells. These features together with the intensity reduction and broadening of the anatase Raman modes imply that the chemical stability of the cell interfaces is accompanied by a modification of the interfacial electric field on the TiO2/dye/electrolyte junction after long-term light and thermal stress.© 2009 American Chemical Society.